Back Extraction of HCl from TOA Dissolved in N-Octanol by Aqueous Ammonia in a Microchannel Device. Issue 1 (2nd January 2016) - Zhao, Fang; Lu, Yangcheng; Wang, Kai; Luo, Guangsheng
Abstract: To recover the extractant in the preparation of KH2 PO4 using the extraction method, studies for the back extraction of HCl by aqueous ammonia from TOA (trioctylamine) dissolved in n-octanol were conducted. First, the reaction of HCl back extraction from TOA in n-octanol with aqueous ammonia was examined in shaking flasks and the equilibrium of this reaction was validated. The equilibrium constant of the stripping reaction was determined in the temperature range of 297.7-318.2 K and the reaction enthalpy was found to be -17.8 kJ/mol indicating that the stripping reaction was exothermic. Then kinetic experiments were performed in a microchannel device with the elimination of mass transfer limitations, as demonstrated by the experimental results. A kinetic model was established to obtain the forward and backward interfacial reaction rate constants with the help of the obtained equilibrium constant of the stripping reaction. This model described the measured data well and predicted correctly the change of HCl concentration in the oil phase along with the residence time in our experiments. Furthermore, the activation energy for the forward (8.21 kJ/mol) and backward (26.0 kJ/mol) reaction was determined and subsequently the forward and backward interfacial reaction rate constants were determined in the temperature range of 298.7-313.2 K.